Ekonomi Kreatif sebagai Anak Panah Politik Hukum Investasi di Indonesia - A Janurita Tenripada; Hari Sutra Disemadi (Legal Spirit, 2023)
Indonesia's potential has made Indonesia a strategic investment destination, both domestic investment and foreign investment. The enormous number of human resources, abundant natural wealth, and various forms of culture that stretch from Sabang to Merauke, have encouraged many potential investors to continue to monitor the development of the Indonesian economy. All of this potential can even continue to increase, if it is put to good use by the creative economy and the industries within it. The global economic recession caused by the COVID-19 pandemic has increased the urgency for the development of the creative economy sector as a sector that has proven its resilience. Using normative legal research methods, this study analyzes Indonesia's ability to facilitate the interests and development of the creative economy in the context of investment. This research outlines the problems contained in the laws and regulations governing investment in Indonesia, as well as their impact on the creative economy in Indonesia. This research also proves that there is an urgency to renew the regulations contained in the laws and regulations governing investment, in order to attract more investors to invest, especially in creative industries.